Knowledge Acquisition Mechanisms during New Technology Implementation Process of Malaysia’s Automotive Engineering Support Industry - Abdullah, Mariam Miri; Othman, Azrina; Mohamad, Norhidayah; Yahaya, Siti Norbaya (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Malaysia’s engineering support industry is crucial in supporting the country’s industry development because it is integrating to other economic sectors including manufacturing, construction, transportation and the primary industry. Players in this industry starting to upgrade their facilities and adopting new technologies to fulfill rigorous requirement of original equipment manufacturers (OEMs) for parts and components along with precision engineering service. Beside technology adoption, knowledge is the main advantage of firm to compete in the turbulence and increasingly complex new business environment. This research aims to explain the specific knowledge acquisition mechanisms used for three knowledge level as proposed by previous researcher. Semi-structured interview was conducted in two participating automotive tooling companies in Selangor to collect data for the study. Thematic analysis was conducted using NVivo. Results of this study found that among the knowledge acquisition mechanisms for declarative knowledge mentioned by the interviewees are basic training, intellectual capital, pre-departure training and instructor manual. The knowledge acquisition mechanisms for procedure knowledge includes external OJT, hiring external expert, related working experience, local training, benchmarking and personal observation. Finally, the knowledge acquisition mechanisms for conditional knowledge includes continuous improvement, learning by doing, project review and trial and error.